2013
DOI: 10.1158/1541-7786.mcr-12-0629
|View full text |Cite|
|
Sign up to set email alerts
|

Procollagen Lysyl Hydroxylase 2 Is Essential for Hypoxia-Induced Breast Cancer Metastasis

Abstract: Metastasis is the leading cause of death among patients who have breast cancer. Understanding the role of the extracellular matrix in the metastatic process may lead to the development of improved therapies to treat cancer patients. Intratumoral hypoxia, found in the majority of breast cancers, is associated with an increased risk of metastasis and mortality. We found that in hypoxic breast cancer cells, HIF-1 activates transcription of the PLOD1 and PLOD2 genes encoding procollagen lysyl hydroxylases that are… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
222
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 229 publications
(233 citation statements)
references
References 63 publications
11
222
0
Order By: Relevance
“…Specific HIF target genes have been identified that are induced by hypoxia in breast cancer cells and promote critical steps in the metastatic process, including stromal cell recruitment (8,9), cancer cell migration (10), invasion and intravasation (11)(12)(13)(14)(15), margination and extravasation (5), and premetastatic niche formation (12,16). Increased expression of HIF target genes in primary breast cancers is associated with increased patient mortality (17,18).…”
mentioning
confidence: 99%
“…Specific HIF target genes have been identified that are induced by hypoxia in breast cancer cells and promote critical steps in the metastatic process, including stromal cell recruitment (8,9), cancer cell migration (10), invasion and intravasation (11)(12)(13)(14)(15), margination and extravasation (5), and premetastatic niche formation (12,16). Increased expression of HIF target genes in primary breast cancers is associated with increased patient mortality (17,18).…”
mentioning
confidence: 99%
“…[36][37][38] Additionally, multiple growth factor receptor pathways, e.g., epidermal growth factor receptor (EGFR), fibroblast growth factor receptor (FGFR), platelet-derived growth factor receptor (PDGFR), and growth factor receptor pathway, were also found to be overrepresented. With angiogenesis being among the enriched processes, the vascular endothelial growth factor receptor (VEGFR) pathway likewise indirectly plays a role in the HLA ligand-dependent functional description of RCC.…”
Section: Discussionmentioning
confidence: 99%
“…20,21,[30][31][32][33][34][35] Furthermore, a vast array of new TAAs with corresponding peptides from HLA class I and II were discovered (Table 3). These included LOX and PLOD2, with high potential in engaging metastasis, [36][37][38] GRB2, ITPR3, and BCAR1, all of which are part of the EGFR pathway 39 and other growth factor receptor pathways, plus ENPEP, NRP2, TGFBI, THBS1, and THBS2, which are essential for angiogenesis. 40 It is notable that 16 out of 24 peptides listed in Table 3 were only found in one tissue sample each.…”
Section: Lc-ms/ms Identifies a High Amount Of Naturally Presented Hlamentioning
confidence: 99%
“…RAB22A gene expression was significantly increased in breast cancers (n = 530) compared with normal breast tissue (n = 63; P < 0.001; Fig 3A). RAB22A expression showed highly significant correlations with the expression of four representative HIF target genes (29,35,36) analyzed, P4HA1, P4HA2, VEGFA, and GLUT1 (P ≤ 0.0007; Fig. 3B).…”
Section: Rab22a Overexpression In Breast Cancer Is Associated With Pamentioning
confidence: 94%
“…In breast cancer, overexpression of HIF-1α or HIF-2α is associated with metastasis, treatment failure, and patient mortality (21)(22)(23)(24)(25)(26). HIFs are required for lymph node and lung metastasis in both autochthonous (27) and orthotopic (28)(29)(30) mouse models of breast cancer and activate the transcription of genes encoding proteins that are required for multiple steps in the invasion and metastasis of breast cancer cells (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38).…”
mentioning
confidence: 99%